Petrologia do stock granítico Glória Sul, Faixa Sergipana, setor sul da Província Borborema, Sergipe - Conceição, Joane Almeida da (2014)
In Sergipana range exists a large volume of granitic rocks, with expression in the Macururé Domain. In this field the granitic bodies are classified as Type Gloria. The Stock Granitic Gloria Sul intruded into the Macururé Domain has an area of approximately 41 km2, with slightly rounded geometry, with rocks showing a large compositional and textural homogeneity, and consist of leucocratic granites whitish mostly stock, showing types of staining gray, equigranular texture. The presence of mafic microgranular enclaves and sometimes it is noticed that the rocks exhibit anisotropic behavior marked by the orientation of mica crystals is evident. Modally rocks of the stock are classified as granites and their enclaves as alkali-feldspar quartz syenite. The rocks have an essential mineralogy consists of quartz, alkali feldspar, plagioclase (albite-oligoclase), muscovite, biotite, diopside and hornblende and magmatic epidote as accessory minerals, sphene, zircon, apatite, carbonate. The chemistry of major elements is characterized by SiO2 contents between 56,38 to 73,19%, Al2O3 from 13,82 to 15,86%, TiO2 from 0,07 to 0,98%, K2O from 1,57 to 7,05%, Na2O between 2,48 to 4,67%, CaO from 0,69 to 5,46%, Fe2O3 from 0,64 to 5,76%, MgO from 0,10 to 4,5%, MnO between 0,01 to 0,12% of P2O5, and 0,02 to 0,58%. The values of the traces show up well differentiated, showing microgranular mafic enclaves that have higher values compared to granite, with levels of Ba variation between 319-1179 ppm, Rb ranging from 55,3 to 351 ppm, Sr ranging from 183,6 to 693,5 ppm, Zr ranging from 54,2 to 224,2 ppm, Nb ranging from 3,4 to 20,8 ppm and Y ranging from 1,6 to 16,7 ppm. These rocks show ETR (ΣETR 38,58 to 299,21 ppm), Lan/Ybn ranging from 12,57 to 137,22 ppm and Eu/Eu* ranging from 0,72 to 1,94 ppm. For a classification of tectonic setting diagram using the parameters Y+Nb versus Rb, studied rocks are positioning themselves in the field of syn-collisional granitoids with the exception of granite with garnet.